2016
DOI: 10.1126/science.aad8995
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of a radical-based reaction by radical S -adenosyl-L-methionine tryptophan lyase

Abstract: The radical S-adenosyl-L-methionine tryptophan lyase NosL converts L-tryptophan into 3-methylindolic acid, which is a precursor in the synthesis of the thiopeptide antibiotic nosiheptide. Using electron paramagnetic resonance spectroscopy and multiple L-tryptophan isotopologues, we trapped and characterized radical intermediates that indicate a carboxyl fragment migration mechanism for NosL. This is in contrast to a proposed fragmentation-recombination mechanism that implied Cα-Cβ bond cleavage of L-tryptophan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 28 publications
4
67
0
Order By: Relevance
“…According to the proposed mechanism, radical 74 could undergo a second β scission forming intermediate 69 which can then tautomerize to form the product ( 62) while radical 70 can form 63 and 64 , as previously proposed. 86 In this regard, NosL differs from other tyrosine lyases (e.g. ThiH), 9 although all start with amino hydrogen abstraction to form 65 .…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…According to the proposed mechanism, radical 74 could undergo a second β scission forming intermediate 69 which can then tautomerize to form the product ( 62) while radical 70 can form 63 and 64 , as previously proposed. 86 In this regard, NosL differs from other tyrosine lyases (e.g. ThiH), 9 although all start with amino hydrogen abstraction to form 65 .…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…(1) These enzymes utilize a [4Fe-4S] + cluster and S -adenosylmethionine (SAM) to catalyze a remarkably diverse array of finely-tuned (2) radical reactions that are central to key pathways, such as heme and chlorophyll biosynthesis, vitamin biosynthesis, DNA repair, and metal cluster assembly. (1) Spectroscopic studies of the radical SAM enzymes pyruvate formate-lyase activating enzyme (PFL-AE) and lysine 2,3-aminomutase (LAM), as confirmed by X-ray structure determinations, demonstrated that these enzymes bind SAM as a classical coordination complex in which the amino and carboxyl moieties of SAM chelate the unique iron of a [4Fe-4S] cluster.…”
mentioning
confidence: 99%
“…Richardson et al study the water hexamer (H 2 O) 6 , which is the smallest cluster with a three-dimensional geometry and has been dubbed the smallest water droplet (3). Advanced spectroscopic methods have yielded experimental information on its structure and properties (4).…”
Section: Pathway 1 Cα-c Cleavagementioning
confidence: 99%
“…There are more than 113,000 radical SAM enzymes, but only a small number are both biochemically and structurally characterized, and many of the reaction mechanisms remain enigmatic. On page 1320 of this issue, Sicoli et al provide evidence for unexpected radical intermediates in the mechanism of the radical SAM enzyme NosL (6).…”
mentioning
confidence: 95%